The Biological Activity of Alhagi Graecorum and Matricaria Chamomilla Extract Against Some Bacteria Causing Urinary Tract Infections - Abbas Khalaf, Assad; K. Mushatet, Mustafa; Jawad Kadhim, Nisreen; Jasim Sahib, Abeer (Kerbala Journal of Nursing and Health Sciences., 2025)
Among the most significant bacteria that cause urinary tract infections were Staphylococcus aureus, Escherichia coli, Psedomonas aeruginosa and Streptococcus pyogenes, all of which are resistant to numerous antibiotics. The continuous hunt for new sources of antimicrobials has been sparked by the rise of microbes resistant to common antibiotics. The leaves and roots of Alhagi graecorum and Matricaria chamomilla were extracted. Each plant extract's antibacterial activity is assessed using the disk diffusion method.are used for detection Minimum inhibition concentration and bactericidal concentration. The ethanol extract of Matricaria chamomilla extract was the most effective against S. aureus and P. aeroginosa, while Alhagi graecorum extract was the most effective against E. coli, and S. pyogen, therefore a viable choice for defense against harmful microbes and can be utilized in the synthesis of antibacterial medicines. In broth microdilution method, the extract of chamomile leaves showed inhibitory effect and the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined as 13.88 and 15 mg/mL, respectively.